Effects of dietary phospholipid and cholesterol levels on growth and fatty acid composition of juvenile swimming crab, Portunus trituberculatus. (3rd March 2017) - Han, T.; Wang, J.T.; Li, X.Y.; Yang, Y.X.; Yang, M.; Tian, H.L.; Zheng, P.Q.; Wang, C.L.
Abstract: The objective of this study was to evaluate the effects of different phospholipids (PL) and cholesterol (CH) levels on the growth, moulting and fatty acid composition of juvenile swimming crab, Portunus trituberculatus . Six diets were designed to contain three PL levels (0, 10 and 20 g/kg) and two CH levels (2 and 8 g/kg). Juvenile swimming crabs (3.48 ± 0.02 g/crab) were reared for 8 weeks. The weight gain (WG) was significantly ( p  <   .05) increased by supplementation of 8 g CH/kg of diet. However, no significant interaction between dietary PL and CH levels was found on the growth performance ( p  > .05). The moulting frequency (MF), protein efficiency ratio (PER) and feed efficiency ratio (FCR) were not significantly ( p  > .05 ) affected by the dietary treatments. The serum total cholesterol (TCH) significantly ( p  > .05 ) increased with increasing dietary PL level. The C20:4n‐6 and C20:5n‐3 content of the whole body of crabs increased with the addition of PL to the diet containing 2 g/kg CH of diet. An interaction was observed between PL and CH on certain saturated and unsaturated fatty acid concentrations of body.